2010
DOI: 10.4028/www.scientific.net/amr.160-162.756
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Core-Shell PA12/Silica Composites Produced by Selective Laser Sintering

Abstract: Silica particles coated with PA12 by emulsion polymerization were used as fillers to reinforce PA12 based composites prepared by selective laser sintering (SLS). The influences of the treated and untreated particles on the sintering behavior and mechanical properties of the laser sintered specimens were investigated. It was found that there were many uneven holes in the untreated composites. However, for the treated composites, due to the silica particle surfaces treated by emulsion polymerization, the absorba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Fillers or additives are encapsulated by crosslinked polymer chains in the emulsion droplets to form composite microcapsules. Paggi et al [151] and Wang et al [121] reported that in an oil/water system, multi-walled CNTs and nanosilica were dispersed in the emulsion droplets of pre-polymer PA12 with the facilitation of chloroform. Zhou et al [135] prepared composite microcapsules through dispersing the carbonated-HA nanoparticles and emulsifier PVA into the PLLAdichloromethane solution.…”
Section: Emulsion-evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fillers or additives are encapsulated by crosslinked polymer chains in the emulsion droplets to form composite microcapsules. Paggi et al [151] and Wang et al [121] reported that in an oil/water system, multi-walled CNTs and nanosilica were dispersed in the emulsion droplets of pre-polymer PA12 with the facilitation of chloroform. Zhou et al [135] prepared composite microcapsules through dispersing the carbonated-HA nanoparticles and emulsifier PVA into the PLLAdichloromethane solution.…”
Section: Emulsion-evaporationmentioning
confidence: 99%
“…Nanocomposites used for harvesting mechanical and electrical energy such as nano-BaTiO3/PA11 via SLS exhibit frequency-dependent dielectric properties that are required by piezoelectrical devices [121]. Nevertheless, the widespread use of AM techniques incorporating nanomaterials, especially in large-scale manufacturing, is still hampered by limited machine capabilities for material digitalization and automatic structural optimization.…”
Section: Energy Storage and Generationmentioning
confidence: 99%
“…The principal advantages of SLS over other polymer AM techniques are as the follows: i) supporting materials are not necessary for building a complex or hollow structure which can be supported by the Chapter 2 Literature review surrounding unfused powders [59][60][61]; ii) a large number of candidate materials are open to the sintering process [62]; iii) the unfused powders are highly recyclable for subsequent builds [63][64][65]. For direct laser-sintered products, ceramics, glass beads and carbon fillers can be employed to reinforce the polymeric matrix for end-use applications or rapid prototyping [25,[66][67][68][69][70][71][72][73]. On the other hand, the laser-sintered polymer/metal or polymer/ceramic composite can be utilized for other post-processes such as moulding, casting, and enhanced-sintering for ceramics and refractory metals to improve the processability and reduce the cost of these processes [74][75][76][77][78].…”
Section: Selective Laser Sinteringmentioning
confidence: 99%
“…Emulsion/solvent evaporation is a process to disperse micro-or nanoparticles into the emulsion system such as a solid-in-oil-water (S/O/W), and then to dry out solvents and precipitate the composite powders simultaneously as shown in Fig. 2.9 [71]. The phase diagram of emulsification is illustrated in Fig.…”
Section: Emulsion Solvent Evaporationmentioning
confidence: 99%
See 1 more Smart Citation